Encyclopaedia of the history of science, technology, and medicine in non-Western cultures - Selin, Helaine 1946- (Springer Reference, 2016)
This updated and augmented third edition of this landmark encyclopedia contains approximately 1000 entries dealing in depth with the history of the scientific, technological and medical accomplishments of cultures outside of the United States and Europe. The entries consist of fully updated articles together with hundreds of entirely new topics adorned with full color pictures. This unique reference work includes intercultural articles on broad topics such as mathematics and astronomy as well as thoughtful philosophical articles on concepts and ideas related to the study of non-Western Science, such as rationality, objectivity, and method. You'll also find material on religion and science, East and West, and magic and science. This amazing resource even contains entries on fascinating esoteric topics such as Native American mathematics, Polynesian navigation, and African Metallurgy. There are also biographical articles for those cultures where individual scientists are known to us, such as China and the Islamic world
Keywords: Geschichte; Technik; Medizin; Naturwissenschaften; Wissenschaft; Außereuropäische Länder; Nichtwestliche Welt; Wörterbuch